2021
DOI: 10.3389/fpls.2020.590179
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Topsoil Root System Architecture in Field-Grown Soybean [Glycine max (L.) Merr.]

Abstract: Water and nutrient acquisition is a critical function of plant root systems. Root system architecture (RSA) traits are often complex and controlled by many genes. This is the first genome-wide association study reporting genetic loci for RSA traits for field-grown soybean (Glycine max). A collection of 289 soybean genotypes was grown in three environments, root crowns were excavated, and 12 RSA traits assessed. The first two components of a principal component analysis of these 12 traits were used as additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…To date, studies have been conducted on the root systems of wheat (Chen et al, 2020), rice (Phung et al, 2016;Kadam et al, 2017;Guimarães et al, 2020), maize (Li et al, 2015), and soybean (Falk et al, 2020;Kim et al, 2021). However, most of these studies were carried out in controlled environments, with the exception of a study of Dhanapal et al (2021), which investigated only the topsoil part of the root system. Phenotyping of roots under controlled conditions, including laboratories or greenhouses, can be done with a large number of genotypes at a reasonable cost.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies have been conducted on the root systems of wheat (Chen et al, 2020), rice (Phung et al, 2016;Kadam et al, 2017;Guimarães et al, 2020), maize (Li et al, 2015), and soybean (Falk et al, 2020;Kim et al, 2021). However, most of these studies were carried out in controlled environments, with the exception of a study of Dhanapal et al (2021), which investigated only the topsoil part of the root system. Phenotyping of roots under controlled conditions, including laboratories or greenhouses, can be done with a large number of genotypes at a reasonable cost.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to earlier GWAS studies, our analysis aligns with past sample sets, typically involving several hundred samples ranging from 137 to 397 varieties (Salim et al 2021;Dhanapal et al 2020;Seck, Torkamaneh, and Belzile 2020;Prince et al 2019;S.-H. Kim et al 2023;Chandnani et al 2023;Falk et al 2020). These studies measured between seven and thirteen traits and identified two to 70 candidate genes, spanning a wide range of annotations (Salim et al 2021;Dhanapal et al 2020;Seck, Torkamaneh, and Belzile 2020;Prince et al 2019;S.-H. Kim et al 2023;Chandnani et al 2023;Falk et al 2020). Our analysis identified overlaps with two specific loci adding to the credibility of the discovered associations.…”
mentioning
confidence: 99%